Scientific Literatures on Conjugated Linoleic Acid (CLA) Research in Ruminant Products: A Bibliometric Study of Evolution and Current Trends - Nursaadah Syahro Fitriyah; Lukman Abiola Oluodo; Patipan Hnokaew; Siriporn Umsook; Tanakorn Tanukarn; Wiphawan Kueamanee; Prayad Thirawong; Trisadee Khamlor; Saowaluck Yammuen-Art (Veterinary Integrative Sciences)
The objective of this study was to analyze the trends in ruminant products research (beef, goat, lamb, and milk) research, particularly conjugated linoleic acid (CLA) using intellectual and conceptual structures in bibliometric analysis. This study was conducted due to limited bibliometric articles despite the ongoing interest in the field. Data was extracted from the Scopus database and visualized using VOSviewer and the bibliometrix R package. The analysis was conducted on 2725 articles published between 2014-2024. The results indicate a decrease in the annual growth of publication in CLA research on ruminant products. Despite this decline, certain key journals persist in their role as primary references for CLA in ruminant products. The analysis revealed predominant topics such as fatty acids, meat quality, and biohydrogenation. However, certain emerging topics, including the application of particular feedstuffs and feed additives to boost fatty acids and CLA levels, have not been thoroughly investigated.